Gui-zhi-fu-ling-wan alleviates bleomycin-induced pulmonary fibrosis through inhibiting epithelial-mesenchymal transition and ferroptosis - Chen, Zi-Yong; Ma, Meng-Meng; Wang, Rui; Zhang, Qing-Qing; Xie, Mei-Ling; Wang, Ying-Li; Guo, Yong-Xia; Liu, Kui; Cao, Li-Fang; He, Feng-Lian; Fu, Lin; Jiang, Ya-Lin (Frontiers in Pharmacology, 2025)
BackgroundIdiopathic pulmonary fibrosis (IPF) has a higher morbidity and poor prognosis. Gui-Zhi-Fu-Ling-Wan (GFW) is a traditional Chinese herbal formula which exerts anti-inflammatory and anti-oxidative effects. The goal was to determine the protective effect of GFW on bleomycin (BLM)-induced pulmonary fibrosis.MethodsOne hundred and twenty-four mice were randomly divided into eight groups, and orally supplemented with GFW (1 g/kg) in 1 week ago and continuing to 1 week later of single BLM intratracheal injection (5.0 mg/kg). Lung tissues were collected in 7 days and 21 days after BLM injection. BEAS-2B cells were pretreated with GFW (100 μg/mL) for three consecutive days before BLM (10 μg/mL) exposure. Cells were harvested in 12 or 24 h after BLM co-culture.ResultsGFW supplementation alleviated BLM-induced alveolar structure destruction and inflammatory cell infiltration in mice lungs. BLM-incurred collagen deposition was attenuated by GFW. In addition, GFW pretreatment repressed BLM-evoked downregulation of E-cadherin, and elevation of N-cadherin and Vimentin in mouse lungs. Besides, BLM-excited GPX4 reduction, ferritin increases, lipid peroxidation, and free iron overload were significantly relieved by GFW pretreatment in mouse lungs and BEAS-2B cells. Notably, BLM-provoked mitochondrial reactive oxygen species (mtROS) excessive production, elevation of mitochondrial stress markers, such as HSP70 and CLPP, and mitochondrial injury, were all abolished in mouse lungs and BEAS-2B cells by GFW pretreatment.ConclusionGFW supplementation attenuated BLM-evoked lung injury and pulmonary fibrosis partially through repressing EMT and mtROS-mediated ferroptosis in pulmonary epithelial cells.